CORRUPTION: SOME ISSUES OF COUNTERACTION - A. A. Ivanova (Russian Journal of Economics and Law, 2016)
Objective: to develop the author’s concept of corruption counteraction.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors that determined the choice of the following research methods: formal-logical, systematic, content analysis.Results: the authors have analyzed and proposed definitions of such notions as: anti-corruption monitoring, corruption counteraction, legal regulation, subjects of counteraction; the main methods of counter-corruption management system evaluation are highlighted. The necessity is grounded to use the data of applied criminological research and the media to prevent and combat corruption, to establish the monitoring mechanisms, in particular, providing the legal and social diagnostics of legal conscience.Scientific novelty: for the first time the article presents and justifies the author's concept of the mechanism of socio-legal control of law enforcement in the aspect of the implementation of its preventive function in the sphere of corruption crimes counteraction.Practical significance: the findings of the article can be used in scientific, educational and law enforcement activities in addressing the issues related to the identification, suppression and prevention of corruption crimes.